PENGARUH MODEL PEMBELAJARAN MATEMATIKA REALISTIK TERHADAP PEMAHAMAN SISWA PADA MATERI BILANGAN BULAT - AINUL MARHAMAH HASIBUAN (JURNAL ILMIAH MAKSITEK, 2020)
This research aims to find out the understanding of students' mathematics before and after using the Realistic MathematicsLearning Model, whether there is an influence on the use of realistic mathematics learning on students' mathematicalunderstanding. This research is a quantitative research experiment. The population of this study is grade IV SD Negeri200211 Padangmatinggi and its sample with two classes namely grades IV-A and IV-B. Instruments used in data collectionare essay tests. The data analysis technique is to use the formula "t" test. Based on normality and homogeneity test results,both sample classes are distributed normally and homogeneously. The t-test result obtained is thitung = 2.79 > ttabel=1.9992, from the calculation is clearly seen ha acceptance and rejection of Ho. The results of this study show that thehypothesis is accepted that there is a significant influence (reassuring) between the use of realistic mathematical learningmodels on students' understanding of integer material in grade IV elementary school.